Introductory fluid mechanics - Katz, Joseph, 1947- (Cambridge University Press, 2010)
"The first objective of this introductory text is to familiarize students who have been exposed to only one course on fluids with the basic elements of fluid mechanics so that, in the event that their future work relies on occasional numerical solutions, they will be familiar with the jargon of the discipline and the expected results. At the same time, this book can serve as a long-term reference text, contrary to the oversimplified approach occasionally used for such introductory courses. The second objective is to provide a comprehensive foundation for more advanced courses in fluid mechanics (within disciplines such as mechanical or aerospace engineering). In order to avoid confusing the students, the governing equations are introduced early, and the assumptions leading to the various models are clearly presented. This provides a logical hierarchy and explains the interconnectivity between the various models. Supporting examples demonstrate the principles and provide engineering analysis tools for many engineering calculations"--